2016
DOI: 10.1007/s11255-016-1437-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronotherapy for hypertension in patients with chronic kidney disease: a systematic review and meta-analysis in non-black patients

Abstract: This meta-analysis suggests that chronotherapy could reduce nocturnal BP in hypertensive CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Although the importance of chronopharmacology in the treatment of hypertension has been studied in several observational trials, only a few of these trials were randomized and controlled and most had major flaws in their design. Meta-analyses on the few existing randomized controlled trials (RCTs) confirmed that blood pressure control is improved by administering anti-hypertensive medications at bedtime in patients with hypertension and/or CKD (121)(122)(123)(124).…”
Section: Kidney Transplantationmentioning
confidence: 99%
“…Although the importance of chronopharmacology in the treatment of hypertension has been studied in several observational trials, only a few of these trials were randomized and controlled and most had major flaws in their design. Meta-analyses on the few existing randomized controlled trials (RCTs) confirmed that blood pressure control is improved by administering anti-hypertensive medications at bedtime in patients with hypertension and/or CKD (121)(122)(123)(124).…”
Section: Kidney Transplantationmentioning
confidence: 99%
“…As a result, the idea of treating patients suffering from hypertension and other cardiovascular diseases with specific time-of-day dosing, otherwise known as chronotherapy, has gained considerable attention in recent years. In nondipping hypertensive patients with chronic kidney disease, bedtime dosing of antihypertensive medications may help reduce nocturnal BP and restore a rhythmic BP pattern, which also correlates with improved long-term prognosis (21,25,43). A study performed in 2,156 hypertensive subjects from a Spanish cohort showed that bedtime therapy with antihypertensive medications improved BP control and decreased the prevalence of nondipping BP (16).…”
Section: Introductionmentioning
confidence: 99%
“…A study on 60 subjects with nonspoon-type blood pressure in CKD showed that although valsartan significantly reduced systolic and diastolic blood pressure before and after bedtime administration, it significantly improved non-spoon-type blood pressure [11]. A meta-analysis also confirmed that time therapy significantly reduced nocturnal systolic and diastolic blood pressure [12]. Nocturnal hypertension and non-spoon-type blood pressure control is improved by this treatment method.…”
mentioning
confidence: 88%